Kinematics and Contact Stress Analysis of Pediatric Anterior Cruciate Ligament Reconstructions: Do the All-Epiphyseal and Complete Transphyseal Reconstructions Restore Anterior and Rotational Stability?. Issue 7 (29th July 2014) - McCarthy, Moira; Jahandar, Hamid; Fabricant, Peter D.; Stone, Kyle; Boorman-Padgett, James; Green, Daniel W.; Imhauser, Carl; Cordasco, Frank A.
Objectives: Pediatric ACL reconstruction techniques have been described that can restore stability and contact pressures to the ACL deficient knee. The complete transphyseal (CT) reconstruction uses a more vertical graft to minimize physeal damage whereas the all-epiphyseal (AE) reconstruction uses sockets beginning at the ACL footprint and avoids the physis. The CT reconstruction may leave the knee unstable against pivot shift loads and leave contact stress abnormalities, whereas the AE may better resist rotational loads. A direct comparison of the kinematics and contact stresses after AE and CT ACL reconstructions have not been studied. Hypotheses: Both the AE and CT reconstructions will restore translational kinematics but the AE technique will better restore rotational kinematics. The AE reconstruction will more closely replicate the contact stresses of the ACL intact knee compared to the CT reconstruction because of the restoration of rotational stability. Methods: Seven fresh-frozen human cadaveric knees were tested using a robotic manipulator. Each of the specimens was tested with the intact ACL, the deficient ACL, and after each reconstruction. The AE utilized sockets oriented within the epiphysis. The CT had more central and vertical sockets in both the tibia and femur. Both reconstructions were fixed with suspensory cortical fixation devices using an all-inside technique and 10 mm diameter hamstring grafts. Reconstruction order was randomized. Anterior stability was assessed with 134N anterior force at 30, 90° of knee flexion simulating the Lachman and anterior drawer exams, respectively. The pivot shift exam was simulated by applying a combined 8 Nm and 4 Nm of abduction and internal rotation, respectively, at 15° of knee flexion. Tibiofemoral motions were recorded and mean contact stresses generated within the tibiofemoral compartments were measured using contact stress transducers. Outcomes were compared across conditions of the ACL using ANOVA and Kruskall-Wallis for normally and non-normally distributed data, respectively. Results: Both reconstructions had significantly decreased anterior translation, medial translation, and internal rotation compared to the ACL deficient knee (Figure 1) in response to loads simulating the pivot shift. However, internal rotation and medial translation remained elevated beyond intact levels following the CT reconstruction by 10.5% (P<0.05) and by 75.3% (P<0.05), respectively. During the simulated anterior drawer test at 30° and 90° of knee flexion both reconstructions restored anterior translation to that of the ACL intact knee. In response to the pivot-shift, the AE reconstruction decreased lateral posterior contact stresses compared to the ACL-deficient knee. However, following CT reconstruction, they remained elevated compared to the ACL-competent knee (P<0.05). Both reconstruction techniques offloaded the posterior aspect of the medial tibial plateau compared to the ACL deficient knee in response to anterior loading at 30 and 90° of knee flexion. Conclusion: While both AE and CT reconstructions reduced anterior translations and posteromedial contact stresses in response to an anterior load, the AE technique more effectively reduced axial rotation and posterolateral contact stresses during a simulated pivot shift exam. These findings are likely due to the more oblique orientation of the AE graft, which makes it a more effective stabilizer to rotational and medial-lateral loads.